Legal Issues Concerning Food Poisoning in Nigeria: The need for Judicial and Statutory Response - Aidonojie, Paul Atagamen; Francis, Esther Chetachukwu (Jurnal Media Hukum, 2000)
Food is essential to man's existence, giving the popular saying that a healthy feeding often determines a healthy living of an individual. However, it has been observed that given the high rate of food insecurity in Nigeria, it has resulted to a high influx of numerous food producers producing substandard products or food that could cause food poisoning. Given this, the study made use of a doctrinal and non-doctrinal method of research method in examining the causes and dangers of food poisoning in Nigeria, how effective statutory laws are, and judicial attitude towards cases of food poisoning. The study adopted an online survey questionnaire distributed to 347 respondents (randomly selected) living in various states in Nigeria. Analytical and descriptive statistics were used to analyze data generated from the online questionnaire. The study, therefore, found that most Nigerians have suffered from food poisoning arising from poor processing, storage, and preservation of harmful substances. It was therefore concluded and recommended that, there is a need for statutory response and judicial activism in curtailing the sale of food that could cause food poisoning. Furthermore, food inspector agencies should often conduct routine inspections of public and private food processing factories or vendors